2014
DOI: 10.1111/nph.12899
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining distances with the engineer: patterns of coexistence in plant communities beyond the patch‐bare dichotomy

Abstract: SummaryTwo-phase plant communities with an engineer conforming conspicuous patches and affecting the performance and patterns of coexisting species are the norm under stressful conditions.To unveil the mechanisms governing coexistence in these communities at multiple spatial scales, we have developed a new point-raster approach of spatial pattern analysis, which was applied to a Mediterranean high mountain grassland to show how Festuca curvifolia patches affect the local distribution of coexisting species.We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 88 publications
6
69
3
2
Order By: Relevance
“…alpina appear interspersed within the community. Previous studies in this community found that neither the dominant F. curvifolia nor the shrub species affect the spatial distribution of S. ciliata (Pescador et al ).…”
Section: Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…alpina appear interspersed within the community. Previous studies in this community found that neither the dominant F. curvifolia nor the shrub species affect the spatial distribution of S. ciliata (Pescador et al ).…”
Section: Methodsmentioning
confidence: 72%
“…50 cm: Lara‐Romero et al ). Pescador et al () observed that habitat heterogeneity in the psychroxerophyllous pastures where this species lives affects its spatial pattern, as some areas had more favourable abiotic conditions for the species’ occurrence. Furthermore, previous studies suggest that adults have a facilitative effect on recruits by providing shade and better soil conditions including the amelioration of water availability (Lara‐Romero et al ).…”
mentioning
confidence: 99%
“…First, for each species’ spatial pattern, we fitted models of fine‐scale spatial distribution that accounted for the effects of environmental heterogeneity and limited dispersal (Pescador et al., ; Jara‐Guerrero et al., ; Chacon‐Labella et al., ; see Supporting information for details). Then, we assessed interspecific spatial associations using bivariate point‐pattern analysis (Baddeley et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Environmental heterogeneity, dispersal and biotic interactions shape the fine‐scale distribution of organisms and affect the spatial structure of populations, communities and ecosystems (Kefi, Rietkerk, van Baalen, & Loreau, ; Meron, ; Rietkerk, Dekker, de Ruiter, & van de Koppel, ). For instance, facilitation can induce fine‐scale associations (Bruno, Stachowicz, & Bertness, ; Chacon‐Labella, de la Cruz, & Escudero, ; Schöb, Kammer, Kikvidze, Choler, & Veit, ) while competition can reduce them (Durrett & Levin, ; MacArthur & Levins, ; Pescador, Chacon‐Labella, de la Cruz, & Escudero, ; Tilman, ). The structure of plant communities can therefore be seen as a complex network of positive and negative interactions among species (Levine, Bascompte, Adler, & Allesina, ; Losapio, Pugnaire, O'Brien, & Schöb, ; Saiz, Gomez‐Gardeñes, Borda, & Maestre, ; Verdù & Valiente‐Banuet, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although χ 2 tests ignore the question of scale, they allow evaluating if P. sylvestris and J. communis individuals grow exactly under J. sabina canopies, an issue that spatial point‐pattern analyses do not fully cover (but see Pescador et al. ).…”
Section: Methodsmentioning
confidence: 99%